The Concept of Quadratic Function Graphs Presented in Singaporean Mathematics Textbooks and Its Potential in Developing Critical Thinking Skills - Nursidrati, Nursidrati; Nasruddin, Nasruddin; Nurlailah, Nurlailah; Muharyati, Yully; Pradita, Diyah Ayu Rizki (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
This study describes how the concept of quadratic function graphs is presented in Singaporean mathematics textbooks and its potential in improving critical thinking skills. The research approach used is descriptive qualitative with critical thinking criteria set by Facione (2015), namely interpretation, analysis, evaluation, and inference . Based on the results of the study, it was found that the presentation of the concept of quadratic function graphs in Singaporean mathematics textbooks, the concept of quadratic function graphs is presented deductively and through investigative activities. As for the potential for presenting the concept of quadratic function graphs, it can develop critical thinking skills. This can be seen from the fulfillment of critical thinking criteria.